'I took care of my kids': mothering while incarcerated - Stephanie C. Kennedy; Annelise M. Mennicke; Chelsea Allen (BMC, 2020)
Abstract Background Little is known about how incarcerated mothers make meaning of their parenting role and relationship with their children prior to incarceration and during custody. The aims of this project were to explore the experiences of mothering prior to incarceration and during custody using the Gendered Pathways Perspective and to examine how mothering intersects with incarcerated women's health and health outcomes to facilitate prevention and intervention strategies. This secondary data analysis used qualitative methods and grounded theory to identify themes related to mothering from 41 incarcerated mothers. Analyses were conducted by two independent coders, each of whom interviewed women as part of the primary study. Results Identified themes highlight how mothers sacrificed their own health and wellness in order to parent their children, sometimes foregoing substance use disorder treatment because they had no childcare options. Additionally, incarcerated mothers described the psychological distress of family separation and asked for additional parenting programs to increase mother-child connection. Finally, mothers suggested that capitalizing on the mothering role might be a potent mechanism for change, especially as related to substance use disorder treatment. Conclusions Research on incarcerated parents often focuses on their children, which obscures incarcerated mothers' needs related to health and wellness. The prison environment offers few opportunities to foster mother-child connection; most mothers never receive even one visit from their children. Incarcerated mothers contextually framed crime as protecting and providing for children and identified community-based and in-prison service gaps. Recommendations include infusing mothering and caretaking responsibilities into the sentencing process and exploring the intersection of race, gender, class, and mothering status on criminalized behavior. Additionally, there is an urgent need to expand the availability of community-based and in-prison programs that allow women to address health concerns while mothering their children.